Poster 246: Comparison of Meniscectomy versus Repair in Bucket Handle Meniscus Tears: Analysis of a Large, Contained Cohort Study. Issue 7 (30th July 2022) - Tucker, Lue-Yen; Vieira, Amy; Ding, David
Objectives: o evaluate the long-term risk of subsequent ipsilateral knee surgery in patients who underwent a bucket handle meniscus repair (BHMR) versus meniscectomy and assess risk factors associated with subsequent knee surgical intervention. Methods: We performed an electronic health records search for all patients who underwent arthroscopic knee meniscus surgery (repair and meniscectomy) from 2011 to 2018. Natural language processing was used to search for terms of interest in the long operative notes to determine if these surgeries were performed for bucket handle meniscus tears. These patients comprised our initial cohort. Study subjects were followed for at least one year and up to five years with censoring at death, membership disenrollment, or 12/31/2019. Baseline patient characteristics and outcomes (i.e., subsequent operative procedures, deep surgical site infections, and deep venous thrombosis) were evaluated via a database review. The primary outcome was subsequent ipsilateral knee surgeries and secondary outcomes included contralateral knee surgeries, deep surgical site infections, and venous thrombotic events. Multivariable logistic regression analyses were used to model for subsequent surgical treatment of the ipsilateral knee. Survival analyses were performed using the Kaplan-Meier method. We then performed a subset analysis for patients 30-50 years-old. Results: The mean follow-up time was 3.9 years (standard deviation [SD] 1.3 years). A total of 1359 patients underwent meniscus repair and 1537 patients underwent meniscectomy for a bucket-handle meniscus tear. The mean age was 27 (SD 10.9) years for the repair group versus 37.5 (SD 13.1) for the meniscectomy group (P<0.001). BMI was significantly lower in the meniscus repair compared to the meniscectomy group (P<0.001). BHMR was significantly more likely to be performed during a concomitant ipsilateral ACL reconstruction than a meniscectomy (44.2% vs 30.1%, P<0.001). During the follow-up period, a total of 656 subsequent ipsilateral procedures were performed in 393 (13.6%) patients. Patient who underwent initial BHMR were at a significantly higher risk to undergo subsequent meniscus repair (4.3% vs 1%, P<0.001), meniscus debridement (12.1% vs 3.3%, P<0.001), and ACL reconstruction (7.4% vs 2.9%, P<0.001) compared to initial meniscectomy. Multivariate analysis showed that BHMR, younger age, and lower BMI were risk factors in subsequent ipsilateral surgery. After adjusting for patient demographic and clinical characteristics, subset analysis showed for age 30-50 year-old patients, undergoing a BHMR versus a meniscectomy led to a 2.3-times higher risk of subsequent surgery, with a 5.3-times higher risk of subsequent meniscus repair and a 3.2-times risk of subsequent meniscectomy. Conclusions: BHMR is more often performed in younger, lower BMI individuals especially during a concomitant ACL reconstruction. BHMR are more likely to undergo subsequent surgeries which decreases with regards to increasing age. Subset analyses showed increasing risk for subsequent surgeries with BHMR versus meniscectomy in the age 30-50 years-old cohort.